2001
DOI: 10.2209/tdcpublication.42.87
|View full text |Cite
|
Sign up to set email alerts
|

Clinicostatistical Study of Ameloblastoma Treatment.

Abstract: The purpose of this study was to investigate the treatment of 190 cases of ameloblastoma in our department from 1966 to 1994. The statistical results with regard to age, sex and region agreed with those of other investigators. Thirty-five of 43 (81.4%) cases underwent enucleation in 1960s, but the sixteen of 27 (59.3%) cases underwent partial resection of mandible in 1990s. The defect of mandible was reconstructed with iliac bone grafting since 1968, grafts with a mixture of iliac blocked bone and PCBM (partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Although others have been able to preserve this nerve and even graft it for reconstruction, so far we have not been able to duplicate their good results. 6 Because of the large size of tumours in our series, the nerve has regularly been sacrificed on the involved side.…”
Section: Discussionmentioning
confidence: 99%
“…Although others have been able to preserve this nerve and even graft it for reconstruction, so far we have not been able to duplicate their good results. 6 Because of the large size of tumours in our series, the nerve has regularly been sacrificed on the involved side.…”
Section: Discussionmentioning
confidence: 99%
“…The male: female ratio was 1.5:1. Hatada et al from Japan documented a mean age of 35 years with a male: female ratio of 1.6:1, with about 93% of tumors located in the mandible [18]. In a study on 52 cases of ameloblastomas from India, the predominant age of presentation was the third to fourth decades with a male preponderance; and the most common site was the lower jaw, especially the posterior aspect, both for new and recurrent cases [19].…”
Section: Epidemiology Of Ameloblastomamentioning
confidence: 99%
“…Lu et al ( 4 ) studied the Chinese populations and showed a mean age of 31.4 years with a 1.5:1 male : female ratio and 90.8% of the tumors were in mandible. A study by Hatada et al ( 5 ) on the Japanese population showed a mean age of 34.7 years with a 1.6:1 male : female ratio and 92.6% was located in the mandible. There was no study found in Indonesian population.…”
Section: Introductionmentioning
confidence: 97%